L’impact politique des flux migratoires dans les États du Conseil de Coopération du Golfe - Philippe Cadène; Brigitte Dumortier (L'Espace Politique)
Arab Gulf countries are now one of the main destination for international migrations at a world level. Although it is difficult to estimate precisely and surely how many people come and stay in the Gulf Cooperation Council States, one can be sure that foreigners are a numerical majority in the active and in the total population of this part of the world. As the Arab component of this immigration is going thinner, Southern Asia remains the first geographical origin of immigrants at all levels of qualification and not only unskilled workers, but a diversification of the recruiting areas is worth to be noted. What is the policy of the local authorities to face the changing migratory realities in the context of globalization? Are the measures concerning the statute of the foreigners more or less similar from a country to the other or are they different? While the governments reinforce a policy to increase the participation of Nationals in the labour force, is the adaptation of laws and practises observed since the beginning of the present decade the sign of a real change towards a better recognition of the contribution of foreigners to the development of the country?